2010
DOI: 10.1210/jc.2010-0019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Exercise Bout on Insulin Sensitivity in Black and White Individuals

Abstract: These data suggest that insulin sensitivity is similar in blacks and age-, sex-, and body mass index-matched whites, but the glucose disposal pathways (storage vs. oxidation) are somewhat different. Compared with whites, blacks appear to have a greater capacity to increase glucose oxidation immediately after exercise and during insulin stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
1
10
2
Order By: Relevance
“…Likewise, insulin sensitivity was increased 12 hours after exercise compared to a no-exercise trial in young men who performed multiple sets of leg resistance exercise [14], and in young overweight men and women who performed an 84-minute cycling session (~3000 kJ) [15]. In agreement with the current study though, insulin sensitivity was not significantly improved in three other investigations in which adults completed 60–75 minutes of moderate intensity cycling, walking and/or rowing (~1250–2100 kJ) 12–17 hours before the postexercise testing was performed [1618]. Thus, exercise volume and/or intensity are likely to be important, but not the only regulators of the magnitude and duration of insulin action response.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Likewise, insulin sensitivity was increased 12 hours after exercise compared to a no-exercise trial in young men who performed multiple sets of leg resistance exercise [14], and in young overweight men and women who performed an 84-minute cycling session (~3000 kJ) [15]. In agreement with the current study though, insulin sensitivity was not significantly improved in three other investigations in which adults completed 60–75 minutes of moderate intensity cycling, walking and/or rowing (~1250–2100 kJ) 12–17 hours before the postexercise testing was performed [1618]. Thus, exercise volume and/or intensity are likely to be important, but not the only regulators of the magnitude and duration of insulin action response.…”
Section: Discussionsupporting
confidence: 83%
“…In Study 2, the exercise energy expenditure of ~1180 kJ during the 45-minute session was lower than typically used (~1250–3350 kJ) in prior single exercise session studies performed with adults [9, 13, 1518, 34]. The lower exercise volume may explain the relatively modest improvement in glucose, insulin, and C-peptide AUC on the Same Day Ex trial and failure for the exercise to exert even a partial effect on the Prior Day Ex trial, or carbohydrate oxidation on either exercise trial.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Among NHB and NHW women, Irwin et al reported similar decreases in fasting insulin levels for every 90 metabolic equivalent (MET)‐min/day change. Another study, conducted by Hasson et al, found no differences in the acute improvements in whole‐body S i comparing NHBs with NHWs following a single 75‐min bout of exercise at 75% V o 2 max. The results of these studies indicate that NHBs and NHW have similar physiological responses in the change in S i from PA.…”
Section: Discussionmentioning
confidence: 92%